1996
DOI: 10.1007/bf02599599
|View full text |Cite
|
Sign up to set email alerts
|

Physician perspectives on the ethical aspects of disability determination

Abstract: Physicians perceive an ethical bind as they try to satisfy the conflicting demands of patients and the welfare disability system. They will frequently decide in favor of their patient's interests. This has implications for welfare policy planners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…It is possible that managing patients in this manner is easier for health care providers with an established relationship with the patient, which at least theoretically should be the case for the PCP, ensuring greater effectiveness in directing patients to resume normal activities. Alternatively, PCPs may avoid potential conflicts about health care or return to work, preferring to acquiesce to patients’ demands [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that managing patients in this manner is easier for health care providers with an established relationship with the patient, which at least theoretically should be the case for the PCP, ensuring greater effectiveness in directing patients to resume normal activities. Alternatively, PCPs may avoid potential conflicts about health care or return to work, preferring to acquiesce to patients’ demands [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible source of variation in disability recommendations may be inadequate medical education or poor preparation of physicians for determining disability (Sullivan and Loeser 1992 ). Indeed, a majority of surveyed physicians indicated that they have learned little about disability programmes from any source (Carey et al 1987 ), do not feel confident in their ability to determine patient disability (Zinn and Furutani 1996 ), and felt burdened by participation in this task (Zinn and Furutani 1996 ). Furthermore, many physicians feel inadequately educated about work capabilities and risk for injury from occupation exposures .…”
Section: Physicians' Characteristics That Influence Disability Recommmentioning
confidence: 99%
“…When surveyed, many doctors admit frequently acting preferentially on behalf of the interests of individual patients 8 9. This suggests a good measure of empathy with patients on the part of physicians, a physician characteristic that has been linked to positive clinical outcomes 10…”
Section: Half-truths and Partialitymentioning
confidence: 99%